Development of a nomogram for predicting early visual acuity outcomes and reoperation rate in patients with open globe injury - Luqian Yang; Shuming Ji; Yan Zhao; Yue Song; Xueni Liu; Hongpei Ji (BMC Ophthalmology)
Abstract Objective We aimed to investigate the occurrence and factors influencing early visual acuity (VA) outcomes and reoperation rates in patients with open globe injuries (OGI) and develop a nomogram for predicting early visual acuity outcomes and reoperation rate. Methods We conducted a retrospective review of data from 121 patients with treated OGI. Relevant information of all patients with OGI were collected after a 1-month timeframe post-surgery. Continuous variables were described using descriptive statistics, while categorical variables were described via frequency distributions between different groups. Model performance was evaluated using receiver operating characteristic (ROC) curve, calibration curve, and decision curve analysis (DCA). Results There were significant differences between patients with reoperation group and patients without reoperation in term of gender, initial visual acuity, length of stay, and Birmingham Eye Trauma Terminology (BETT) types of injury. The result showed that initial VA, laterality, the BETT types of injury, location, retinal detachment, orbital CT, and intraoperative changes were related to the VA outcome, and initial VA is the most significant factor. Constructed nomogram based on those variables had a good efficiency in predicting the VA outcome. We obtained eight variables related to reoperation, including initial VA, age, length of stay, Gender, BETT, iris prolapse, retinal detachment, and type of anesthesia, and age is the most important factor. The nomogram based on those variables had a good efficiency for predicting the reoperation. Furthermore, the DCA showed that utilizing a reference threshold of 0.71 for VA outcomes and 0.79 for reoperation rates may offer clinical net benefit. Conclusions Our models showcase significant predictive efficacy in evaluating early VA outcome and reoperation rate, offering valuable insights to ophthalmologists in their clinical decision-making endeavors.